Mine own executioner - Meredith, Burgess 1907-1997; Gray, Dulcie 1915-2011; Balchin, Nigel 1908-1970 (Network, 2015)
Meredith stars as Felix Milne, a lay psychiatrist in post-war London who is enlisted to treat Adam Lucian, a fighter pilot deeply traumatised by his experiences in a Japanese prisoner-of-war-camp. Beleaguered by emotional problems of his own, Milne embodies the mixture of dedication, self-distrust and self-criticism that characterises someone with a genuine vocation for the psychiatrist's work; but is he qualified to treat a patient as disturbed and potentially destructive as Adam?"
DVD of the 1947 motion picture
Full screen (1.33:1)
Special Features: Image gallery, promotional material pdfs
Keywords: Psychologists / Drama; Ex-prisoners of war / Drama; Self-doubt / Drama; Feature films; Fiction films; Film adaptations; Psychologists; Self-doubt; Drama; Film; Blu-Ray-Disc